Effects of carbohydrate restriction on strength performance - Leveritt, M.; Abernethy, P. J. (The Journal of Strength and Conditioning Research, 1999)
This study investigated the effect of a carbohydrate restriction program on performance in a bout of isoinertial and isokinetic strength exercise. One female and five male subjects (mean ± SD: age = 20.3 ± 2.3 years; body mass = 74.6 ± 11.5 kg; height = 177.0 ± 8.8 cm) performed isoinertial and isokinetic strength exercise under control conditions (no experimental intervention) and after a 2-day carbohydrate restriction program. The carbohydrate restriction program consisted of 60 minutes of cycling at 75% of peak cycle ergometer oxygen consumption (PVo2), followed by four 1-minute bouts at 100% of PVo2, followed by 2 days of reduced carbohydrate intake (1.2 ± 0.5 g·kg1·d1). Isoinertial strength exercise was three sets of squats with a load of 80% of one repetition maximum. Isokinetic strength exercise was five repetitions of leg extensions performed at five different contractile speeds (1.05, 2.09, 3.14, 4.19, and 5.24 rad·s1). The carbohydrate restriction program caused a significant reduction in the number of squat repetitions performed. Torque at 0.52 rad from full extension (T30) was not significantly altered by carbohydrate restriction. Plasma lactate concentration postexercise was significantly lower after carbohydrate restriction. The fact that carbohydrate restriction reduces performance in isoinertial but not isokinetic strength exercise may be due to the different metabolic demands associated with the different exercise protocols used in the two modes of strength exercise.